Analysis of self-healing of depression by helping others in adolescents from the perspective of constructivism - Xin, Zhonggui; Li, Shuguang; Jia, Yanxian; Yuan, Hui (Frontiers in Psychiatry, 2023)
Purpose This study aims to explore the mechanism of psychological qualities constructed in helping others with depression and guide adolescents to actively participate in the practical activities of helping others to prevent and self-heal depression. Method Symptom self-rating scale, trait coping style questionnaire, and self-administered helper scale were employed. A total of 1,086 valid on-site questionnaires were collected from adolescents. Result The depression levels of adolescents were negatively correlated with helping beliefs, behaviors and total scores (r = −0.500, −0.401, and −0.530). Helping others had a significantly negative predictive effect on depression, effectively inhibiting depression levels. Although the positive coping style had an inhibitory effect on depression, it exerted no predictive effects on depression under the influence of helping others. In contrast, the negative coping style had a significantly positive predictive effect on depression. Conclusion Proactively participating in helping others is an important way to prevent and eliminate depression in adolescents. They should be instructed to give full play to their initiatives to participate in social practice and assist others actively, thus constructing positive psychological qualities, improving mental health, and achieving self-healing of depression and self-help through helping others.